2020
DOI: 10.1093/clinchem/hvz005
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Point-of-Care Measurements of Maternal Glucose for the Diagnosis of Gestational Diabetes Mellitus

Abstract: Background Point-of-care (POC) measurement of glucose is currently recommended only for the monitoring of gestational diabetes mellitus (GDM). This prospective observational study evaluated the use of POC measurements of maternal glucose to diagnose GDM in women being screened selectively with a 1-step 75 g oral glucose tolerance test (OGTT). Methods The strictest preanalytic and analytic international laboratory standards we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Correct pre-analytic sampling of plasma glucose is important to prevent glycolysis and to prevent false negative results. A recent study of O'Malley showed that fluoride tubes must be stored on ice or must be centrifuged within 30 min to prevent glycolysis [55].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Correct pre-analytic sampling of plasma glucose is important to prevent glycolysis and to prevent false negative results. A recent study of O'Malley showed that fluoride tubes must be stored on ice or must be centrifuged within 30 min to prevent glycolysis [55].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The incidence of GDM was 53% ( n = 108) applying the 2013 WHO criteria, 35% ( n = 71) applying Canadian criteria and 18% ( n = 36) applying the UK NICE criteria 5 . We also found that some women who were treated pharmacologically based on the WHO criteria would not have been treated based on the other two sets.…”
Section: Figurementioning
confidence: 78%
“…We recently published a study which compared three different sets of diagnostic criteria using the one‐step 75 g OGTT at 26–28 weeks gestation in an Irish population screened selectively based on maternal risk factors 3 . The preanalytical laboratory standards for the study were more stringent than those applied for the Hyperglycemia and Adverse Pregnancy Outcomes (HAPO) study 4–6 …”
Section: Figurementioning
confidence: 99%
“…Furthermore, the use of point-of-care testing versus laboratory testing are also highly relevant to consider when examining and comparing GDM prevalence. Malley et al showed that the diagnostic accuracy of a point-of-care measurement versus a laboratory measurement was 83% (74.2%-89.8%) [37], suggesting that if the tests are performed in resource-rich settings, then the use of blood collection tubes containing citrate that inhibits glycolysis followed by laboratory tests are preferable. However, in low-resource settings such as Tanzania where this procedure is not always possible, it will be relevant to validate point-of-care testing with laboratory testing if new screening procedures are going to be implemented.…”
Section: Discussionmentioning
confidence: 99%